PENGUJIAN USABILITY SISTEM INFORMASI PELAYANAN RUKUN WARGA MENGGUNAKAN USE QUESTIONNAIRE - Esron Rikardo Nainggolan; Susafa’ati Susafa’ati (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
In order to create complacency and success of an information system that has been created, a test is needed, one of them is usability testing on the system to be implemented. This testing is done by analyzing the usability aspects of a system. Usability aspects to be tested including Usefulness, Satisfaction, and Ease of use. The purpose of this research is to determine the acceptance of usability web-based citizen services system by measuring the dimensions of usefulness, satisfaction, and ease of use. This research used a testing method with USE Questionnaire which consists of 30-Question. This research is a descriptive quantitative research conducted on Rusunawa RW 014 Pesakih by survey method. The test results showed the average variable value is 4.18 and was in the Interval of Assessment